Institutional Constraints on Investigative Oversight: Accountability and Governance of the Investigation Supervision Bureau (Biro Pengawas Penyidikan) of the Indonesian National Police - Sinaga, Mastalina; Prativi, Dhiajeng (Jurnal Kriminologi Indonesia, 2026)
Investigative professionalism constitutes a fundamental pillar of the criminal justice system; however, its realization is frequently constrained by institutional design and procedural limitations within oversight mechanisms. This article examines the role of the Investigation Supervision Bureau (Biro Pengawas Penyidikan (Birowassidik)) of the Criminal Investigation Agency (Badan Reserse Kriminal (Bareskrim)) of the Indonesian National Police (Polri) in handling public complaints related to investigative performance. Rather than presuming the existence of a unified ‘Code of Silence’, this study adopts a qualitative critical analysis to assess the structural and procedural constraints inherent in Birowassidik’s mandate as a complaint-based supervisory institution. The analysis demonstrates that the low resolution rate of public complaints (34.1% as of December 2025) should not be interpreted as conclusive evidence of organizational collusion or subcultural loyalty, but instead reflects evidentiary dependency, jurisdictional fragmentation, and limitations in supervisory authority. Accordingly, the concept of the ‘Code of Silence’ is treated as an analytical hypothesis rather than an empirical conclusion. This study argues that strengthening investigative accountability requires a recalibration of governance expectations through enhanced procedural transparency, digital oversight mechanisms such as e-SP2HP, and clearer institutional coordination with other internal and external oversight bodies. Such an approach is essential to ensuring accountability that is both realistic and consistent with the principles of good governance and democratic legal certainty.